AKUNTABILITAS PENGELOLAAN DANA ZAKAT DIGITAL DAN PENGARUHNYA TERHADAP KEPERCAYAAN PUBLIK TERHADAP SISTEM FISKAL - Afrial Insani; Andi Muhammad Yudhistira; Almas Sabila Putri; Devi Oktaviani; Firmansyah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Advancements in digital technology have transformed zakat management through various digital payment and collection platforms. While this digitalization offers convenience for the public in fulfilling their zakat obligations, it also necessitates accountable governance to maintain public trust. Accountability is a crucial aspect, as it relates to the transparency, reporting, and responsibility of zakat management institutions in handling funds collected from the public. This study aims to analyze the impact of accountability in digital zakat fund management on public trust in the fiscal system. A quantitative approach was employed, utilizing a survey of individuals who have used digital zakat services. Data were analyzed using linear regression to examine the relationship between the accountability of digital zakat fund management and public trust in the fiscal system. Accountability indicators included financial report transparency, ease of access to information, regulatory compliance, and the effectiveness of zakat fund distribution. Meanwhile, public trust was measured based on public perceptions regarding the integrity, credibility, and professionalism of zakat management institutions. The findings confirm that accountability in digital zakat fund management has a positive and significant impact on public trust in the fiscal system. Higher levels of transparency and accountability demonstrated by digital zakat management institutions correlate with greater public trust in the management of public funds in general. These findings indicate that strengthening accountability in digital zakat management can serve as a strategy to enhance public trust and support the creation of better fiscal governance in the digital era.